2020
DOI: 10.1007/s12471-020-01453-7
|View full text |Cite
|
Sign up to set email alerts
|

Progress in heart failure management in the Netherlands and beyond: long-term commitment to deliver high-quality research and patient care

Abstract: Heart failure (HF) remains a major global problem. In the Netherlands, 1.5-2.0% of the total population is diagnosed with HF. Over 30,000 HF patients are admitted annually in the Netherlands, and this number is expected to further increase given the ageing population and the chronic nature of HF. Despite ongoing efforts to reduce the burden of HF, morbidity and mortality rates of this disease remain high. However, several new treatment modalities have become available or are expected to become available in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“… 20 , 21 To ensure systematic and coordinated treatments, DMPs for HF have been implemented on a national level. 22 These cover care in hospitals, outpatient clinics or at home. 23 , 24 More recently, the Connect programme aims at implementing agreements across primary, secondary and tertiary care at regional levels to improve HF-care.…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 21 To ensure systematic and coordinated treatments, DMPs for HF have been implemented on a national level. 22 These cover care in hospitals, outpatient clinics or at home. 23 , 24 More recently, the Connect programme aims at implementing agreements across primary, secondary and tertiary care at regional levels to improve HF-care.…”
Section: Resultsmentioning
confidence: 99%
“…Within cardiology, previous research has shown that there are meaningful differences between the sexes in clinical characteristics and therapeutic responses to different treatments [ 35 ]. A possible explanation for the difference is the higher prevalence of HF with preserved ejection fraction (HF-pEF) among female patients, which has limited treatment options compared to HF with reduced ejection fraction (HF-rEF) [ 36 ]. Fewer medical treatment options may translate into less need for remote monitoring of titration of medication [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite therapeutic advances and ongoing research, advanced heart failure remains associated with frequent hospital admissions, poor prognosis and high costs [1][2][3]. As patients with advanced heart failure often suffer pronounced functional decline and poor quality of life, they could benefit from palliative care [4].…”
Section: Introductionmentioning
confidence: 99%